The epidemiology of Cryptosporidium species in a Nigerian paediatric population - Molloy, Síle F. (Trinity College (Dublin, Ireland). Department of Zoology, 2009)
Cryptosporidium is an Apicomplexan, protozoan parasite, infecting the gastroepithelium of many vertebrate hosts, including man, and is the causative agent of the diarrhoeal disease cryptosporidiosis. Although infection may be asymptomatic or mild and self-limiting in immunocompetent patients, in the immunocompromised (especially the malnourished and those with HIV/AIDS), the disease can be severe, leading to chronic dehydration and even death (Dillingham etai., 2002).
Keywords: Zoology, Ph.D.; Ph.D. Trinity College Dublin.